2003
DOI: 10.1097/00000542-200308000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breathing Improves Lung Aeration in Oleic Acid–induced Lung Injury

Abstract: The results support the hypothesis that spontaneous breathing during APRV improves oxygenation mainly by recruitment of nonaerated lung and improved aeration of the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 33 publications
5
119
1
4
Order By: Relevance
“…We could not completely exclude a possible influence of the instrumental apparatus used for the pneumoperitoneum induction on hemodynamics. Nevertheless, its impact on the edema formation, if any, is questionable because the excess tissue mass recorded under these conditions was similar or even smaller than previously reported (29,31).…”
Section: Oleic Acid-injured Lungsupporting
confidence: 43%
See 1 more Smart Citation
“…We could not completely exclude a possible influence of the instrumental apparatus used for the pneumoperitoneum induction on hemodynamics. Nevertheless, its impact on the edema formation, if any, is questionable because the excess tissue mass recorded under these conditions was similar or even smaller than previously reported (29,31).…”
Section: Oleic Acid-injured Lungsupporting
confidence: 43%
“…Although the rise in Ppa has been already described in different experimental settings (27)(28)(29), the increase in mean arterial and occlusion pressures has not been previously reported (30). We could not completely exclude a possible influence of the instrumental apparatus used for the pneumoperitoneum induction on hemodynamics.…”
Section: Oleic Acid-injured Lungmentioning
confidence: 72%
“…As described above, the APRV methodologies were subdivided into two categories: F-APRV; (Tables 1 and 3) and P-APRV (Tables 2 and 4). The majority of the animal studies (69 % of total) [2,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and human studies (82 % of total) [3, were in the F-APRV category.…”
Section: Methodsmentioning
confidence: 99%
“…Many crossover trials showed similar or increased oxygenation with lower peak pressures and no negative effect on hemodynamics with APRV as compared with CPPV [2,3,17,[27][28][29][30][31][32][39][40][41][42], and some studies showed hemodynamic improvement with APRV [13,24,36,39]. Prospective randomized trials comparing APRV and CPPV showed that APRV is safe and potentially beneficial (Table 3).…”
Section: Outcomementioning
confidence: 99%
“…The study demonstrated that increases in tidal volume with positive-pressure ventilation failed to alter V D /V T , suggesting greater dead space from overdistention of al- Experiments in a porcine model have further defined the advantages of spontaneous breathing in enhancing ventilation perfusion relationships and oxygenation. 56,57 Using both computed tomography and a ␥ camera technique, one group demonstrated that lung injury with oleic acid resulted in a predictable fall in end-expiratory lung volume and oxygenation. Animals were either maintained on controlled ventilation or allowed to breathe up to 30% of the total minute volume spontaneously.…”
Section: The Importance Of Spontaneous Breathingmentioning
confidence: 99%